Group action and other representative actions: differentiating criteria - Губська, Алла Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The questions of correlation of group action and other types of representative actions are probed in the article. In science of civil procedure there are a few scientific doctrines to the decision of correlation of such concepts as a «group action», «derivative action», «action, on defence of rights and interests of indefinite persons». The author gives a conclusion, that all these actions are separate types of representative actions. Criterion for their differentiating is orientation of interest which is subject defence at application of certain type of these actions.